Analysis of the Effects of Family Support and Intention on Compliance with Medication in Patients with Hypertension - Rizki, Ahmat Kurniawan; Fikriana, Riza; Agustiningsih, Nia (International Journal of Psychosocial Rehabilitation, 2020)
Hypertension is commonly dubbed as a silent killer. There are no typical symptoms so it is difficult to recognize someone who has hypertension and is unaware. The purpose of this study was to analyze the effect of family support and intention on medication adherence in patients with hypertension. The research design used is cross-sectional. The population in this study were all patients with hypertension in the Talangagung Village Kepanjen District Malang Regency with purposive sampling that was adjusted to the criteria so there were 100 hypertensive patients in the research sample. Data collection was carried out using a family support questionnaire, intention questionnaire and medication compliance questionnaire (Questionnaire Morisky 8-item Medication Adherence Questionnaire). Data analysis was done using Linear Regression Test (α<0.05). The results found that the intention variable had a significant effect on adherence to taking medication with the result of a significance value (p= 0.000); however, the value of the family support (p= 0.272) means that it does not significantly influence medication adherence in patients with hypertension. It can be seen that intention is one of the factors that can affect medication adherence, so in order to increase the compliance to take medication it is necessary to increase patients’ intention.